Formulation Studies in Multiphase Emulsion Systems (Journal of Science and Technology, 2016)
The potential of multiple water-in-oil-in-water (w/o/w) emulsions as a drug carrier is dependent upon the extent of multiple droplet formation, the integrity of the multiphase structure formed, and the localisation of the drug or the biologically active agent in the inner-most phase. The studies indicate that predominantly stable multiple w/o/w droplets can be obtained with specific ternary compositions. As the two-step method is used in the preparation of these emulsions, a drug can be localised within the internal aqueous phase by incorporating it in the disperse phase of the primary w/o emulsion, and hence these systems can function as vehicles or carriers for drugs.